SEM-PLS Untuk Analisis Struktur Kemiskinan Pada Masa Pandemi Covid-19 - Rahma Rahma Nuryanti; Tulus Soebagijo (Seminar Nasional Official Statistics, 2021)
The Covid-19 pandemic has had various impacts, especially on the economic aspect. This difficult economic condition causes people's income to decrease, and causes the number of poor people to increase. The number of poor people increased by 1.28 million people in 2020. East Java Province is a province that has a poverty rate (10.20 percent) slightly higher than the national (10.19 percent) in 2020. This is due to the impact of the pandemic. leading to job losses and increased poverty rates. This study will analyze the structure of poverty in East Java Province in 2020. The purpose of this study is to see the structure of poverty in East Java Province in 2020. The analytical method used in this study is component-based Structural Equation Modeling (SEM), namely Partial Least Square. (PLS). In the structural equation model there are 4 significant paths, namely the effect of health variables on the education variable, the effect of health and education variables on the economy, and the influence of economic variables on the poverty variable. The results of the Grouping Analysis with Finite Mixture Partial Least Square based on the Akaike Information Criterion (AICk), Consistent Akaike Information Criterion (CAICk) and Bayesian Information Criterion (BICk) and Normal Entrophy (EN) criteria, the best results were 2 segments. So that from 38 regencies/cities in East Java Province, they can be grouped into 2 segments. The First Segment is 91.9 percent of the total regencies/cities, and the Second Segment is 8.1 percent of the total regencies/cities in the East Java region. The regencies/cities in the second segment are Situbondo Regency, Nganjuk Regency and Kediri City. Meanwhile, 35 other regencies/cities are in the first segment.